Ionophoretic Study of Mixed Ligand Complexes of Mn(II), Pb(II) and Th(VI)-Adenosine Triphosphate Nitrilotriacetate System - Yadav, Sudha; Yadava, K.L. (Asian Journal of Chemistry, 2010)
Use of paper electrophoresis has been described for the study of metal-ligand equilibria in solution. This technique is based on the movement of a spot of metal ion under an electric field with the complexant added in the background electrolyte at a fixed pH 8.5. The concentration of primary ligand adenosine triphoshate (ATP) was kept constant while that of secondary ligand nitrilotriacetate (NTA) was varied. Valuable information is obtained from the plots of -log [NTA] against mobility regarding the mixed complexes. The overall stability constants of the M-ATP-NTA have been found to be 1010.09, 1010.39 and 1011.64 for mixed ligand complexes of Mn(II), Pb(II) and Th(IV) respectively at u = 0.1 and temperature 30 ± 0.1°C.